Approximating Common Fixed Points of Nonspreading-Type Mappings and Nonexpansive Mappings in a Hilbert Space. (30th August 2012) - Kim, Kyung Soo
Abstract : We obtain some fundamental properties for k -strictly pseudo-nonspreading mappings in a Hilbert space. We study approximation of common fixed points of k -strictly pseudo-nonspreading mappings and nonexpansive mappings in a Hilbert space by using a new iterative scheme. Furthermore, we suggest some open problems.